2020
DOI: 10.1186/s12957-019-1778-2
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a nomogram for preoperative prediction of lymph node metastasis in early gastric cancer

Abstract: Background: The status of lymph nodes in early gastric cancer is critical to make further clinical treatment decision, but the prediction of lymph node metastasis remains difficult before operation. This study aimed to develop a nomogram that contained preoperative factors to predict lymph node metastasis in early gastric cancer patients. Methods: This study analyzed the clinicopathologic features of 823 early gastric cancer patients who underwent gastrectomy retrospectively, among which 596 patients were recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 40 publications
3
19
1
Order By: Relevance
“…The incidence of lymph node metastasis in our study was 17.33%, which is similar to previous studies (Pereira et al, 2018;Yin et al, 2020;Mei et al, 2021). Although our study confirmed that lymphovascular invasion and perineural invasion were risk factors for lymph node metastasis in patients with EGC, clinicians could not obtain evidence of lymphovascular invasion and perineural invasion in the period of preoperative evaluation; thus, it was not included in the multivariate model.…”
supporting
confidence: 85%
“…The incidence of lymph node metastasis in our study was 17.33%, which is similar to previous studies (Pereira et al, 2018;Yin et al, 2020;Mei et al, 2021). Although our study confirmed that lymphovascular invasion and perineural invasion were risk factors for lymph node metastasis in patients with EGC, clinicians could not obtain evidence of lymphovascular invasion and perineural invasion in the period of preoperative evaluation; thus, it was not included in the multivariate model.…”
supporting
confidence: 85%
“…However, few molecular markers have proven useful in diagnosing lymph node metastasis in actual clinical specimens. These include VEGF-C (43,44), EGFR (99), E-cadherin (100, 101), CD44v6 (102), and p53 (103,104). Unfortunately, these are still in the research stage and have not yet been used in clinical practice.…”
Section: An Attempt To Predict Lymph Node Metastasis In Early Gastric Cancer By Using Nomogram and Molecular Makersmentioning
confidence: 99%
“…For example, miR-489 overexpression can inhibit the survival, invasion, and migration of gastric cancer cells, and circulating lncRNAs play an important role in the early diagnosis of GC [ 34 , 35 ]. Furthermore, the clinical results of gastric cancer can be predicted by constructing nomogram [ 36 ].…”
Section: Discussionmentioning
confidence: 99%